Differentiated Thyroid Cancer, From Active Surveillance to Advanced Therapy: Toward a Personalized Medicine - Matrone, Antonio; Campopiano, Maria Cristina; Nervo, Alice; Sapuppo, Giulia; Tavarelli, Martina; De Leo, Simone (Frontiers in Endocrinology, 2020)
Differentiated Thyroid Carcinoma (DTC) is the most frequent endocrine malignancy and represents the most rapidly increasing human cancer worldwide. In the last 20 years, the increased diagnosis of DTC has been mostly due to a higher detection of small papillary thyroid cancers, with doubtful effects on patients’ outcome. In fact, despite this growth, cancer-related death remained stable over the years. The increased detection of microcarcinomas associated to the indolent behavior of these cancers, led to the development of strategies of active surveillance, in selected centers of different countries. Moreover, towards a more personalized approach in the management of DTC patients, surgical treatments became more conservative, preferring less extensive options in patients at low risk of recurrence. The rise of lobectomy in low risk cases and the need to avoid further therapies, with controversial impact on recurrences and cancer related death in selected intermediate risk cases, led to reconsider the use of radioiodine treatment, too. Since clinicians aim to treat different patients with different modalities, the cornerstone of DTC follow up (i.e., thyroglobulin, thyroglobulin autoantibodies and neck ultrasound) should be interpreted consistently with this change of paradigm. The introduction of novel molecular target therapies (i.e. tyrosine kinase inhibitors) is radically changing the management of patients with advanced DTC, in whom no treatment option was available. The aim of this review is to analyze the most recent developments of the management of DTC, focusing on several key issues: active surveillance strategies, initial treatment, dynamic risk re-stratification, and therapeutic options in advanced DTC.